High-strength superfine denier nylon 66 filament and preparation method thereof

Through the use of solid-phase tackification, humidity regulation and nanomodifiers, combined with technical means such as melt extrusion and multi-stage filtration, the existing nylon 66 fiber preparation methods are solved, and high-strength is successfully prepared , High-strength ultrafine denier nylon 66 filament with good stability.

CN119465423AActive Publication Date: 2025-02-18ZHONGWEI CHEM FIBER CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411551640.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-02-18
Estimated Expiration
2044-11-01

AI Technical Summary

Technical Problem

The existing nylon 66 fiber preparation method is complex, the process is unstable, and the product performance is poor, especially the low strength and unstable physical properties, which affect the performance of subsequent products.

Method used

Using solid-phase tackification and humidity-regulating nylon 66 spinning-level slices, added nanomodifier, and through melt extrusion, multi-stage filtration, pressurized spinning, cooling, oiling, drafting and winding, etc. Steps to prepare high-strength ultrafine denier nylon 66 filaments.

Benefits of technology

The prepared high-strength ultrafine denier nylon 66 filaments have high mechanical strength, low denier number, small heat shrinkage, uniform and stable wire strips, low production cost, good comprehensive performance, and are suitable for a variety of application fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005115246240000131
    Figure BDA0005115246240000131
Patent Text Reader

Abstract

The invention provides a high-strength superfine denier nylon 66 filament and a preparation method thereof, and belongs to the technical field of nylon. The high-strength superfine denier nylon 66 filament is prepared by performing solid-phase tackifying and humidifying on nylon 66 spinning-grade slices, adding a nano modifier, performing melt extrusion, performing multi-stage filtration, then performing pressurized spinning, cooling, oiling, drafting and sizing, and winding, thereby obtaining the high-strength superfine denier nylon 66 filament. The high-strength superfine denier nylon 66 filament prepared by the invention has the advantages of higher mechanical strength, lower denier number, small thermal shrinkage rate, uniform and stable filament, lower production cost, excellent comprehensive performance and wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nylon, and in particular to a high-strength ultra-fine denier nylon 66 filament and a preparation method thereof. Background Art

[0002] Nylon 66, also known as polyhexamethylene adipamide or PA66, is an excellent engineering plastic with high strength, friction resistance, high temperature resistance, corrosion resistance and other characteristics. It is widely used in the two major fields of engineering plastics and synthetic fibers, especially in the fields of automobiles, electronics and electrical, rail transportation, etc. It has a significant consumption share. The monomers of nylon 66, adipic acid and hexamethylenediamine, are mainly derived from petroleum and are prepared by polymerization reaction.

[0003] The nylon 66 industry began to be industrialized in 1939 and is widely used in the fields of chemical fibers and engineering plastics. In particular, in the past 10 years, the world's nylon consumption has increased at an average annual rate of about 7.5%. As a type of engineering plastic, nylon is widely used in military textiles, industry, clothing, decoration, engineering plastics and other fields.

[0004] High-strength ultra-fine denier nylon 66 fiber has the advantages of high strength, good rigidity, impact resistance, oil and chemical resistance, wear resistance and self-lubrication, especially better hardness, rigidity, heat resistance and creep performance. However, its preparation method is complicated, the preparation process is unstable, and the performance of the prepared product is poor.

[0005] Chinese patent document CN101871134A discloses a fine denier nylon 66 fully drawn fiber spinning production process, which adopts the spinning process of slice and primary drawing method (a pair of hot rollers), without heat relaxation and heat setting, and produces 11dtex / 7f nylon 66 fiber with a strength of 5.2cN / dtex. The nylon 66 fiber produced by this patent has low strength and cannot meet the needs of some use fields with high strength requirements; in addition, the production process disclosed in this patent only adopts primary drawing, without relaxation and heat setting, which may lead to unstable physical properties of the produced fiber, especially after moisture absorption, its strength decreases significantly, affecting the performance of subsequent products. Summary of the invention

[0006] The purpose of the present invention is to provide a high-strength ultra-fine denier nylon 66 filament and a preparation method thereof, which has high mechanical strength, low denier, small thermal shrinkage, uniform and stable filaments, low production cost, good comprehensive performance and broad application prospects.

[0007] The technical solution of the present invention is achieved in this way:

[0008] The invention provides a method for preparing high-strength ultra-fine denier nylon 66 filaments. The method comprises the following steps: solid-phase viscosity enhancement and moisture adjustment are performed on nylon 66 spinning-grade slices, a nano-modifier is added, the filaments are melt-extruded, multi-stage filtered, pressurized spun, cooled, oiled, drawn and shaped, and wound to obtain high-strength ultra-fine denier nylon 66 filaments.

[0009] As a further improvement of the present invention, the following steps are included:

[0010] S1. Solid phase viscosity enhancement and humidity control: solid phase viscosity enhancement and humidity control treatment are performed on nylon 66 spinning grade chips to obtain nylon 66 medium-high viscosity chips;

[0011] S2. Melt extrusion: The high viscosity slices of nylon 66 are sent to a screw extruder, a nano-modifier is added, and melt extrusion is performed;

[0012] S3. Filtration spinning: The melt is filtered through multiple stages, and then the booster pump is pressurized and transported to the spinning box, and then metered by the metering pump and spun through the spinning assembly;

[0013] S4. Cooling: The filaments are cooled by side blowing to form a filament bundle;

[0014] S5. Oiling: The cooled tow is oiled to eliminate static electricity;

[0015] S6. Drafting and shaping: Drafting and shaping the oiled tow;

[0016] S7. Winding: Wind the shaped filament bundle into a filament tube to obtain high-strength ultra-fine denier nylon 66 filament.

[0017] As a further improvement of the present invention, the relative viscosity of the nylon 66 spinning-grade chips in step S1 is 2.2-2.3, the water content of the nylon 66 medium-high viscosity chips is 650-750ppm, and the relative viscosity is 3.3-3.5, and the solid phase viscosity enhancement is performed on the chips at 140-170°C using nitrogen for countercurrent circulation; the amount of the nano modifier added in step S2 is 2-3wt%, and the temperature of the melt extrusion is 280-300°C.

[0018] As a further improvement of the present invention, the preparation method of the nano modifier is as follows:

[0019] T1. Preparation of carbon-deposited nano-silica: adding nano-mesoporous silica to water, adding ferric chloride, stirring and adsorbing, centrifuging, washing, drying, introducing n-hexane under inert gas protection, heating and reacting to obtain carbon-deposited nano-silica;

[0020] T2. Preparation of modified nano-silica: adding carbon-deposited nano-silica to water, adding dopamine hydrochloride and a catalyst, heating and stirring to react, centrifuging, washing, and drying to obtain modified nano-silica;

[0021] T3. Preparation of a composite mixed solution: adding graphene oxide and sodium benzoate to water, hydrothermally reacting to obtain a composite mixed solution;

[0022] T4. Coating: Add modified nano-silica into the composite mixed solution, stir and react, centrifuge, wash, and dry to obtain a nano-modifier.

[0023] As a further improvement of the present invention, the particle size of the nano-mesoporous silica in step T1 is 150-250 nm, the mass ratio of the nano-mesoporous silica to ferric chloride is 10:1-2, the ventilation volume of n-hexane is 0.2-0.4 mL / min, the temperature of the heating reaction is 600-700°C, and the time is 25-35 min.

[0024] As a further improvement of the present invention, the mass ratio of the carbon-deposited nano-silica, dopamine hydrochloride and catalyst in step T2 is 12-15:3-5:0.5-1, the catalyst is a Tris-HCl solution with a pH of 8.5-9.5, the temperature of the heating and stirring reaction is 40-50°C, and the time is 2-3h.

[0025] As a further improvement of the present invention, the mass ratio of graphene oxide and sodium benzoate in step T3 is 10:3-5, the temperature of the hydrothermal reaction is 65-75°C, and the time is 20-24h; the mass ratio of the modified nano-silica and the composite mixed liquid in step T4 is 9-11:30-50, the temperature of the stirring and mixing reaction is 35-45°C, and the time is 1-2h.

[0026] As a further improvement of the present invention, the fineness of the filaments sprayed out by the spinneret in step S3 is 0.02-0.05mm, and the multi-stage filtration is performed in sequence by suction filtration system filtration and multi-layer filtration device filtration, and the multi-layer filtration device is tightly combined with a layer of sand and a layer of mesh in sequence, and the last layer is tightly combined with the spinneret below; the amount of oil attached in step S5 is controlled to be 0.5-1.5%; the stretching and shaping in step S6 is achieved by 1 stage preheating, 2 stages stretching, and 2 stages shaping between six pairs of hot rollers: wherein the temperature of the first pair of hot rollers is 30-40°C, and the temperature of the second pair of hot rollers is 45-55°C, the first pair of hot rollers and the second pair of hot rollers preheat the filaments, and the stretching ratio is 1-1.01 times; the winding speed in step S7 is 3000-4000m / min.

[0027] The present invention further protects a high-strength ultra-fine denier nylon 66 filament prepared by the above-mentioned preparation method.

[0028] As a further improvement of the present invention, the breaking strength is 12-15 g / D and the denier is 15-25D.

[0029] The present invention has the following beneficial effects:

[0030] The present invention performs primary filtration on the melt flowing in the melt storage chamber through an exhaust fan, and then penetrates into the filtration tube in the melt storage chamber to guide out the filtered impurities, thereby achieving the purpose of removing impurities such as fine particles and oil mist on the surface of the melt and in the cavity; the melt after filtration flows into the flow hole through the discharge port at the lower end of the storage chamber, and enters a multi-layer filtration device composed of a layer of sand and a layer of mesh, which is tightly combined and evenly staggered, and is tightly combined with the spinneret below, thereby ensuring the thickness and flatness of the metal sand, avoiding migration, and making the high-pressure sprayed wire strips more uniform and stable.

[0031] The invention transports the original nylon slices into a drying tower for solid-phase drying and viscosity enhancement, so that the slices reach the high-viscosity slices required by spinning, and then the dried slices are subjected to humidity adjustment treatment to stabilize the moisture content to 650-750ppm. Within the suitable moisture content range, the polymerization reaction of the polymer is regulated, and after the amide groups of the nylon form hydrogen bonds with water molecules, the formed nylon yarns can have a good effect of changing the mechanical properties, so that the elongation at break and the impact strength are increased, and at the same time, the material is expanded, thereby reducing its denier, thereby obtaining ultra-fine denier nylon yarns. The treated slices are then melt-extruded by a screw extruder, and in the melt conveying process, a booster pump is used to pressurize the slices under high pressure to a spinning box, and the slices are metered by a metering pump and then sprayed by a spinning assembly, and the filaments are cooled by low-temperature side blowing to form a tow, and the cooled tows are oiled to eliminate static electricity, and then they are drawn and shaped, and finally wound into a tow on a winding machine.

[0032] The crystallization rate of nylon materials is low, the crystal morphology and size are difficult to control, and the product size stability is low. Adding nucleating agents can increase the crystallization rate of nylon materials and also improve their mechanical strength.

[0033] The present invention adds a nano modifier during the melt extrusion process. The nano modifier uses inorganic nano-mesoporous silica as a core, is a good inorganic nucleating agent for nylon materials, has low cost and has a good enhancement effect on the mechanical properties of nylon materials, but has poor compatibility with nylon materials and is difficult to be uniformly dispersed in the nylon material matrix, resulting in low nucleation efficiency. Carbon materials are deposited on the surface through chemical vapor deposition, which greatly improves the mechanical modification effect on nylon materials, and after being modified with polydopamine, its dispersibility in nylon materials is improved, and it can be well composite-coated with graphene oxide and sodium benzoate, thereby obtaining a stable nano modifier.

[0034] Graphene oxide has good compatibility with nylon materials, but direct addition of it is easy to agglomerate and affect the mechanical improvement of nylon materials. By mixing graphene oxide and sodium benzoate, the uniform dispersion of nanofillers is achieved, and effective contact promotes the formation of a thermal conductive network, thereby improving its thermal conductivity. It is coated on the surface of modified nano-silica, which promotes the dispersion and compatibility of the nano-modifier in nylon materials, and it is not easy to agglomerate itself, which helps to improve the mechanical properties and heat dissipation properties of the material and reduce thermal shrinkage.

[0035] The high-strength ultra-fine denier nylon 66 filaments prepared by the invention have high mechanical strength, low denier, small heat shrinkage, uniform and stable filaments, low production cost, good comprehensive performance and broad application prospects. DETAILED DESCRIPTION

[0036] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] Nano-mesoporous silica, with an average particle size of 200 nm; graphene oxide, with a purity of >99%, a thickness of <5 nm, and an average sheet diameter of 20 μm, were purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.

[0038] Preparation Example 1 Preparation of Nano-Modifier

[0039] The following steps are involved:

[0040] T1. Preparation of carbon-deposited nano-silica: 10 g of nano-mesoporous silica was added to 200 mL of water, 1 g of ferric chloride was added, and the mixture was stirred and adsorbed for 20 min, centrifuged, washed, dried, and passed n-hexane under nitrogen protection at a flow rate of 0.2 mL / min. The mixture was heated to 600 ° C and reacted for 25 min to obtain carbon-deposited nano-silica.

[0041] T2. Preparation of modified nano-silica: 12 g of carbon-deposited nano-silica was added to 200 mL of water, 3 g of dopamine hydrochloride and 0.5 g of catalyst were added, heated to 40° C., stirred for reaction for 2 h, centrifuged, washed, and dried to obtain modified nano-silica;

[0042] The catalyst is a Tris-HCl solution with a pH of 8.5;

[0043] T3. Preparation of the composite mixed solution: 1 g of graphene oxide and 0.3 g of sodium benzoate were added to 100 mL of water and subjected to hydrothermal reaction at 65 ° C for 20 h to obtain a composite mixed solution;

[0044] T4. Coating: Add 9 g of modified nano-silica into 30 g of the composite mixed solution, stir and react at 35° C. for 1 h, centrifuge, wash, and dry to obtain a nano-modifier.

[0045] Preparation Example 2 Preparation of Nano-Modifier

[0046] The following steps are involved:

[0047] T1. Preparation of carbon-deposited nano-silica: 10 g of nano-mesoporous silica was added to 200 mL of water, 2 g of ferric chloride was added, and the mixture was stirred and adsorbed for 20 min, centrifuged, washed, dried, and passed n-hexane under nitrogen protection at a flow rate of 0.4 mL / min. The mixture was heated to 700 ° C and reacted for 35 min to obtain carbon-deposited nano-silica.

[0048] T2. Preparation of modified nano-silica: 15 g of carbon-deposited nano-silica was added to 200 mL of water, 5 g of dopamine hydrochloride and 1 g of catalyst were added, heated to 50° C., stirred for 3 h, centrifuged, washed, and dried to obtain modified nano-silica;

[0049] The catalyst is a Tris-HCl solution with a pH of 9.5;

[0050] T3. Preparation of the composite mixed solution: 1 g of graphene oxide and 0.5 g of sodium benzoate were added to 100 mL of water and subjected to hydrothermal reaction at 75 ° C for 24 h to obtain a composite mixed solution;

[0051] T4. Coating: Add 11 g of modified nano-silica into 50 g of the composite mixed solution, stir and react at 45° C. for 2 h, centrifuge, wash, and dry to obtain a nano-modifier.

[0052] Preparation Example 3 Preparation of Nano-Modifier

[0053] The following steps are involved:

[0054] T1. Preparation of carbon-deposited nano-silica: 10 g of nano-mesoporous silica was added to 200 mL of water, 1.5 g of ferric chloride was added, stirred and adsorbed for 20 min, centrifuged, washed, dried, and n-hexane was introduced under nitrogen protection at a flow rate of 0.3 mL / min. The mixture was heated to 650°C and reacted for 30 min to obtain carbon-deposited nano-silica.

[0055] T2. Preparation of modified nano-silica: 13 g of carbon-deposited nano-silica was added to 200 mL of water, 4 g of dopamine hydrochloride and 0.7 g of catalyst were added, heated to 45 ° C, stirred for 2.5 h, centrifuged, washed, and dried to obtain modified nano-silica;

[0056] The catalyst is a Tris-HCl solution with a pH of 9;

[0057] T3. Preparation of the composite mixed solution: 1 g of graphene oxide and 0.4 g of sodium benzoate were added to 100 mL of water and subjected to hydrothermal reaction at 70 ° C for 22 h to obtain a composite mixed solution;

[0058] T4. Coating: Add 10 g of modified nano-silica into 40 g of the composite mixed solution, stir and react at 40° C. for 1.5 h, centrifuge, wash, and dry to obtain a nano-modifier.

[0059] Comparative Preparation Example 1

[0060] Compared with Preparation Example 3, the difference is that step T1 is not performed.

[0061] The details are as follows:

[0062] T1. Preparation of modified nano-silica: 13 g of nano-silica was added to 200 mL of water, 4 g of dopamine hydrochloride and 0.7 g of catalyst were added, heated to 45 ° C, stirred for 2.5 h, centrifuged, washed, and dried to obtain modified nano-silica;

[0063] The catalyst is a Tris-HCl solution with a pH of 9;

[0064] T2. Preparation of the composite mixed solution: 1 g of graphene oxide and 0.4 g of sodium benzoate were added to 100 mL of water and subjected to hydrothermal reaction at 70° C. for 22 h to obtain a composite mixed solution;

[0065] T3. Coating: Add 10 g of modified nano-silica into 40 g of the composite mixed solution, stir and react at 40° C. for 1.5 h, centrifuge, wash, and dry to obtain a nano-modifier.

[0066] Comparative Preparation Example 2

[0067] Compared with Preparation Example 3, the difference is that step T2 is not performed.

[0068] The details are as follows:

[0069] T1. Preparation of carbon-deposited nano-silica: 10 g of nano-mesoporous silica was added to 200 mL of water, 1.5 g of ferric chloride was added, stirred and adsorbed for 20 min, centrifuged, washed, dried, and n-hexane was introduced under nitrogen protection at a flow rate of 0.3 mL / min. The mixture was heated to 650°C and reacted for 30 min to obtain carbon-deposited nano-silica.

[0070] T2. Preparation of the composite mixed solution: 1 g of graphene oxide and 0.4 g of sodium benzoate were added to 100 mL of water and subjected to hydrothermal reaction at 70° C. for 22 h to obtain a composite mixed solution;

[0071] T3. Coating: Add 10g of carbon-deposited nano-silica into 40g of the composite mixed solution, stir and react at 40°C for 1.5h, centrifuge, wash, and dry to obtain a nano-modifier.

[0072] Comparative Preparation Example 3

[0073] Compared with Preparation Example 3, the difference is that sodium benzoate is not added in step T3.

[0074] The details are as follows:

[0075] T3. Preparation of graphene oxide liquid: 1.4 g of graphene oxide was added to 100 mL of water to prepare graphene oxide liquid.

[0076] Comparative Preparation Example 4

[0077] Compared with Preparation Example 3, the difference is that steps T3 and T4 are not performed.

[0078] The details are as follows:

[0079] T1. Preparation of carbon-deposited nano-silica: 10 g of nano-mesoporous silica was added to 200 mL of water, 1.5 g of ferric chloride was added, stirred and adsorbed for 20 min, centrifuged, washed, dried, and n-hexane was introduced under nitrogen protection at a flow rate of 0.3 mL / min. The mixture was heated to 650°C and reacted for 30 min to obtain carbon-deposited nano-silica.

[0080] T2. Preparation of modified nano-silica: 13 g of carbon-deposited nano-silica was added to 200 mL of water, 4 g of dopamine hydrochloride and 0.7 g of catalyst were added, heated to 45° C., stirred for reaction for 2.5 h, centrifuged, washed, and dried to obtain modified nano-silica, i.e., a nano-modifier;

[0081] The catalyst is a Tris-HCl solution with a pH of 9.

[0082] Example 1

[0083] This embodiment provides a method for preparing high-strength ultra-fine denier nylon 66 filaments, comprising the following steps:

[0084] S1. Solid phase viscosity enhancement and humidity control: solid phase viscosity enhancement and humidity control treatment are performed on nylon 66 spinning grade chips with a relative viscosity of 2.2 to obtain nylon 66 medium-high viscosity chips with a water content of 650ppm and a relative viscosity of 3.3; the solid phase viscosity enhancement is performed on the chips at 140°C with nitrogen countercurrent circulation;

[0085] S2 melt extrusion: The high viscosity slice of nylon 66 was sent to a screw extruder, and the nano-modifier prepared in Preparation Example 1 was added in an amount of 2wt%, and melt extruded at 280°C;

[0086] S3. Filtration spinning: The melt is filtered through multiple stages, and then the booster pump is pressurized and transported to the spinning box, and then metered by the metering pump and spun through the spinning assembly. The fineness of the spun wire is 0.02mm;

[0087] The multi-stage filtration is performed sequentially by the suction filtration system and the multi-layer filtration device, wherein the multi-layer filtration device is composed of a layer of sand and a layer of mesh which are tightly combined in sequence, and the last layer is tightly combined with the spinneret below;

[0088] S4. Cooling: The filaments are cooled by side blowing to form a filament bundle;

[0089] S5. Oiling: The cooled tow is oiled to eliminate static electricity, and the amount of oil is controlled to be 0.5%;

[0090] S6. Drafting and shaping: Drafting and shaping the oiled filaments; this is achieved by 1-stage preheating, 2-stage stretching, and 2-stage shaping between six pairs of hot rollers: the temperature of the first pair of hot rollers is 30°C, the temperature of the second pair of hot rollers is 45°C, the first pair of hot rollers and the second pair of hot rollers preheat the filaments, and the stretching ratio is 1 times;

[0091] S7. Winding: Wind the shaped filament bundle into a filament tube at a winding speed of 3000 m / min to obtain high-strength ultra-fine denier nylon 66 filament.

[0092] Example 2

[0093] This embodiment provides a method for preparing high-strength ultra-fine denier nylon 66 filaments, comprising the following steps:

[0094] S1. Solid phase viscosity enhancement and humidity control: solid phase viscosity enhancement and humidity control treatment are performed on nylon 66 spinning grade chips with a relative viscosity of 2.3 to obtain nylon 66 medium-high viscosity chips with a water content of 750ppm and a relative viscosity of 3.5; the solid phase viscosity enhancement is performed on the chips at 170°C with nitrogen countercurrent circulation;

[0095] S2 melt extrusion: The high viscosity slice of nylon 66 was sent to a screw extruder, and the nano-modifier prepared in Preparation Example 2 was added in an amount of 3wt%, and melt extruded at 300 ℃;

[0096] S3. Filtration spinning: The melt is filtered through multiple stages, and then the booster pump is pressurized and transported to the spinning box, and then metered by the metering pump and spun through the spinning assembly. The fineness of the spun wire is 0.05mm;

[0097] The multi-stage filtration is performed sequentially by the suction filtration system and the multi-layer filtration device, wherein the multi-layer filtration device is composed of a layer of sand and a layer of mesh which are tightly combined in sequence, and the last layer is tightly combined with the spinneret below;

[0098] S4. Cooling: The filaments are cooled by side blowing to form a filament bundle;

[0099] S5. Oiling: The cooled tow is oiled to eliminate static electricity, and the amount of oil is controlled to be 1.5%;

[0100] S6. Drafting and shaping: Drafting and shaping the oiled filaments; this is achieved by 1-stage preheating, 2-stage stretching, and 2-stage shaping between six pairs of hot rollers: the temperature of the first pair of hot rollers is 40°C, the temperature of the second pair of hot rollers is 55°C, the first pair of hot rollers and the second pair of hot rollers preheat the filaments, and the stretching ratio is 1.01 times;

[0101] S7. Winding: Wind the shaped filament bundle into a filament tube at a winding speed of 4000 m / min to obtain high-strength ultra-fine denier nylon 66 filament.

[0102] Example 3

[0103] This embodiment provides a method for preparing high-strength ultra-fine denier nylon 66 filaments, comprising the following steps:

[0104] S1. Solid phase viscosity enhancement and humidity control: solid phase viscosity enhancement and humidity control treatment are performed on nylon 66 spinning grade chips with a relative viscosity of 2.25 to obtain nylon 66 medium-high viscosity chips with a water content of 700 ppm and a relative viscosity of 3.4; the solid phase viscosity enhancement is performed on the chips at 155°C with nitrogen countercurrent circulation;

[0105] S2 melt extrusion: The high viscosity slice of nylon 66 was sent to a screw extruder, and the nano-modifier prepared in Preparation Example 3 was added in an amount of 2.5wt%, and melt extruded at 290°C;

[0106] S3. Filtration spinning: The melt is filtered through multiple stages, and then the booster pump is pressurized and transported to the spinning box, and then metered by the metering pump and spun through the spinning assembly. The fineness of the spun wire is 0.03mm;

[0107] The multi-stage filtration is performed sequentially by the suction filtration system and the multi-layer filtration device, wherein the multi-layer filtration device is composed of a layer of sand and a layer of mesh which are tightly combined in sequence, and the last layer is tightly combined with the spinneret below;

[0108] S4. Cooling: The filaments are cooled by side blowing to form a filament bundle;

[0109] S5. Oiling: The cooled tow is oiled to eliminate static electricity, and the amount of oil is controlled to be 1%;

[0110] S6. Drafting and shaping: Drafting and shaping the oiled filaments; this is achieved by 1-stage preheating, 2-stage stretching, and 2-stage shaping between six pairs of hot rollers: the temperature of the first pair of hot rollers is 35°C, the temperature of the second pair of hot rollers is 50°C, the first pair of hot rollers and the second pair of hot rollers preheat the filaments, and the stretching ratio is 1.005 times;

[0111] S7. Winding: Wind the shaped filament bundle into a filament tube at a winding speed of 3500 m / min to obtain high-strength ultra-fine denier nylon 66 filament.

[0112] Comparative Example 1

[0113] Compared with Example 3, the difference is that the nano modifier is prepared by Comparative Preparation Example 1.

[0114] Comparative Example 2

[0115] Compared with Example 3, the difference is that the nano modifier is prepared by Comparative Preparation Example 2.

[0116] Comparative Example 3

[0117] Compared with Example 3, the difference is that the nano modifier is prepared by Comparative Preparation Example 3.

[0118] Comparative Example 4

[0119] Compared with Example 3, the difference is that the nano modifier is prepared by Comparative Preparation Example 4.

[0120] Comparative Example 5

[0121] Compared with Example 3, the difference is that no nano modifier is added.

[0122] Comparative Example 6

[0123] Compared with Example 3, the difference is that no multi-layer filtration device filtration is performed.

[0124] Comparative Example 7

[0125] Compared with Example 3, the difference is that the water content after humidity adjustment is 300 ppm.

[0126] Test Example 1

[0127] The high-strength and ultra-fine denier nylon 66 filaments prepared in Examples 1-3 of the present invention and Comparative Examples 1-7 were subjected to performance tests. The results are shown in Table 1.

[0128] Table 1

[0129]

[0130] It can be seen from the above table that the high-strength ultra-fine denier nylon 66 filaments prepared in Examples 1-3 of the present invention have good comprehensive properties.

[0131] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing high-strength ultra-fine denier nylon 66 filament, characterized in that: The nylon 66 spinning grade chips are solid-phase thickened and humidified, nano-modifiers are added, melt extruded, multi-stage filtered, pressurized spun, cooled, oiled, drawn and shaped, and wound to obtain high-strength ultra-fine denier nylon 66 filaments.

2. The preparation method according to claim 1, characterized in that: The following steps are involved: S1. Solid phase viscosity enhancement and humidity control: solid phase viscosity enhancement and humidity control treatment are performed on nylon 66 spinning grade chips to obtain nylon 66 medium-high viscosity chips; S2. Melt extrusion: The high viscosity slices of nylon 66 are sent to a screw extruder, a nano-modifier is added, and melt extrusion is performed; S3. Filtration spinning: The melt is filtered through multiple stages, and then the booster pump is pressurized and transported to the spinning box, and then metered by the metering pump and spun through the spinning assembly; S4. Cooling: The filaments are cooled by side blowing to form a filament bundle; S5. Oiling: The cooled tow is oiled to eliminate static electricity; S6. Drafting and shaping: Drafting and shaping the oiled tow; S7. Winding: Wind the shaped filament bundle into a filament tube to obtain high-strength ultra-fine denier nylon 66 filament.

3. The preparation method according to claim 2, characterized in that: The relative viscosity of the nylon 66 spinning-grade chips in step S1 is 2.2-2.3, the water content of the nylon 66 medium-high viscosity chips is 650-750ppm, and the relative viscosity is 3.3-3.

5. The solid phase viscosity enhancement is performed on the chips at 140-170°C using nitrogen countercurrent circulation; the amount of the nano modifier added in step S2 is 2-3wt%, and the temperature of the melt extrusion is 280-300°C.

4. The preparation method according to claim 3, characterized in that: The preparation method of the nano modifier is as follows: T1. Preparation of carbon-deposited nano-silica: adding nano-mesoporous silica to water, adding ferric chloride, stirring and adsorbing, centrifuging, washing, drying, introducing n-hexane under inert gas protection, heating and reacting to obtain carbon-deposited nano-silica; T2. Preparation of modified nano-silica: adding carbon-deposited nano-silica to water, adding dopamine hydrochloride and a catalyst, heating and stirring to react, centrifuging, washing, and drying to obtain modified nano-silica; T3. Preparation of a composite mixed solution: adding graphene oxide and sodium benzoate to water, hydrothermally reacting to obtain a composite mixed solution; T4. Coating: Add modified nano-silica into the composite mixed solution, stir and react, centrifuge, wash, and dry to obtain a nano-modifier.

5. The preparation method according to claim 4, characterized in that: The particle size of the nano-mesoporous silica in step T1 is 150-250 nm, the mass ratio of the nano-mesoporous silica to ferric chloride is 10:1-2, the ventilation rate of n-hexane is 0.2-0.4 mL / min, the temperature of the heating reaction is 600-700° C., and the time is 25-35 min.

6. The preparation method according to claim 4, characterized in that: The mass ratio of the carbon-deposited nano-silica, dopamine hydrochloride and catalyst in step T2 is 12-15:3-5:0.5-1, the catalyst is a Tris-HCl solution with a pH of 8.5-9.5, the temperature of the heating and stirring reaction is 40-50° C., and the time is 2-3 hours.

7. The preparation method according to claim 4, characterized in that: In step T3, the mass ratio of graphene oxide to sodium benzoate is 10:3-5, the temperature of the hydrothermal reaction is 65-75°C, and the time is 20-24h; in step T4, the mass ratio of modified nano-silicon dioxide to the composite mixed liquid is 9-11:30-50, the temperature of the stirring and mixing reaction is 35-45°C, and the time is 1-2h.

8. The preparation method according to claim 2, characterized in that: The fineness of the filaments sprayed out by the spinneret in step S3 is 0.02-0.05mm, and the multi-stage filtration is performed in sequence by the suction filtration system and the multi-layer filtration device, wherein the multi-layer filtration device is tightly combined with a layer of sand and a layer of mesh in sequence, and the last layer is tightly combined with the spinneret below; the amount of oil attached in step S5 is controlled to be 0.5-1.5%; the drawing and shaping in step S6 is achieved by 1-stage preheating, 2-stage stretching, and 2-stage shaping between six pairs of hot rollers: wherein the temperature of the first pair of hot rollers is 30-40°C, and the temperature of the second pair of hot rollers is 45-55°C, the first pair of hot rollers and the second pair of hot rollers preheat the filaments, and the stretching ratio is 1-1.01 times; the winding speed in step S7 is 3000-4000m / min.

9. A high-strength ultra-fine denier nylon 66 filament obtained by the preparation method according to any one of claims 1 to 8.

10. The high-strength ultra-fine denier nylon 66 filament according to claim 9, characterized in that: Its breaking strength is 12-15g / D and its denier is 15-25D.

Citation Information

Patent Citations

  • Fine denier nylon 66 full-draft fiber spinning production process

    CN101871134A

  • Preparation method of low-shrinkage polyamide 66 industrial yarn

    CN106367817A

  • Preparation technology for whitening low-shrinking medium-fine nylon yarns

    CN106435794A

  • Dyeing-free chinlon 66 industrial color silk and preparation method thereof

    CN107829160A

  • Aerogel modified polyamide filament and preparation method thereof

    CN113201803A